Improving students’ achievement in reading comprehending through imaginative text for the eighth grade of SMP Kristen Sa’dan - Meisiana Meisiana; Judith Ratu Tandi Arrang (Teaching English as a Foreign Language Overseas Journal, 2022)
The objective of this research is to find out whether using imaginative text can improve students’ reading achievement in comprehending reading imaginative text or not. In order to achieve the objective of the research, the writer designed an experimental research by using pre-test, treatment and post-test. The population of this study was the eighth grade students at SMP Kristen Sa’dan. Toraja Utara. The population of this study consists of 75 students. The sample of the study was the eighth grade students class B. The number of the students was 25. They took it by using cluster sampling. There were four four meetings. Before the treatment the students were given a pre-test. and after , the students were given a post-test. The result of this research revealed that the post test was higher than pre-test. It could be seen by comparing their mean score. The mean score of the pre-test was 51,4 categorized poor and the mean score of the post-test was 66,6 categorized good. It can be concluded that the eighth grade students of SMP Kristen Sa’dan have good comprehension, after learning to read imaginative texts. Using imaginative text in teaching reading can help the students to improve their comprehension.